2017
DOI: 10.1016/j.pedneo.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Three-year follow-up of children with abnormal newborn screening results for congenital hypothyroidism

Abstract: Earlier re-evaluation might be possible when a patient's initial NST-TSH levels and maximal or 2-year LT4 doses are low, as both are important predictors of successful trial-off therapy in CH patients. When the initial serum level of free T4 is above the average value in neonates with mildly elevated TSH levels, TFTs may be more likely to normalize on their own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 24 publications
0
27
1
2
Order By: Relevance
“…However, the optimal cut-off in this study was 30.5 IU/L. Kang and coworkers reported a similar TSH cut-off point of 31 IU/L for distinguishing TCH and PCH ( 17 ). Other studies suggested initial TSH cut-off values of 28.4 IU/L and 34 IU/L ( 14 , 18 ).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, the optimal cut-off in this study was 30.5 IU/L. Kang and coworkers reported a similar TSH cut-off point of 31 IU/L for distinguishing TCH and PCH ( 17 ). Other studies suggested initial TSH cut-off values of 28.4 IU/L and 34 IU/L ( 14 , 18 ).…”
Section: Discussionmentioning
confidence: 52%
“…Patients with TCH exhibited significantly lower TSH and higher T 4 levels at the time of diagnosis compared to those with PCH. Some previous studies in the literature reported that the initial T 4 did not differentiate between TCH and PCH cases ( 13 , 17 , 22 ).…”
Section: Discussionmentioning
confidence: 85%
“…In Korea, a total of 13 laboratories perform the NBS TSH, and the cutoff levels of TSH vary from 10.0 to 22.5 mIU/mL according to each laboratory protocol (8). Another recent study from Korea showed that nearly 80% of preterm infants with CH treated for 3 years with thyroxine were later diagnosed with transient hypothyroidism (9 (11).…”
Section: Epidemiologymentioning
confidence: 99%
“…Also, transient hypothyroidism tends to respond to a lower dosage of L-T4 than CH. 7,15,24,25 Kashiwagura et al 26 successfully administered a suppository preparation of L-T4 in patients with hypothyroidism who could not take thyroid hormones by mouth. Because our patient was incapable of receiving oral administration of L-T4 and because intravenous and suppository preparations of L-T4 were not available at our hospital, we decided to empirically administer a rectal diluted solution of L-T4.…”
Section: Discussionmentioning
confidence: 99%